2017
DOI: 10.1111/add.13712
|View full text |Cite
|
Sign up to set email alerts
|

Trends in serious quit attempts in the United States, 2009–14

Abstract: Background and aims Quitting smoking is the most potent way to reduce the health risks associated with smoking cig-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In the years when e-cigarette use increased the most, quit attempts also increased. 119–122 Studies from the UK converge with US studies indicating e-cigarettes have increased quitting smoking over and above what would have otherwise been expected. 17,94,113,116,123 Some patterns of infrequent e-cigarette use or even past use measured at one point in time may be (mistakenly) called “dual use” leading to overestimates of chronic dual use.…”
Section: Making a Population Impact: Modeling State Transitions To Chmentioning
confidence: 98%
“…In the years when e-cigarette use increased the most, quit attempts also increased. 119–122 Studies from the UK converge with US studies indicating e-cigarettes have increased quitting smoking over and above what would have otherwise been expected. 17,94,113,116,123 Some patterns of infrequent e-cigarette use or even past use measured at one point in time may be (mistakenly) called “dual use” leading to overestimates of chronic dual use.…”
Section: Making a Population Impact: Modeling State Transitions To Chmentioning
confidence: 98%
“…Surveys of e-cigarette users consistently indicate that, for most smokers, quitting cigarettes is one major reason for ANDS use (41), even among youth (125). In the years when e-cigarette use increased the most, studies revealed a rise in quit attempts (5,40), along with either a steady or faster drop in cigarette use among both youth and adults rather than a slowing of prevalence reduction (21,82). Studies suggest that daily users of e-cigarettes for a month or more are six times more likely to have quit smoking cigarettes two years later (11); former smokers who quit less than one year prior are four times more likely to be daily e-cigarette users compared with current smokers (26); and studies from the United Kingdom suggest that e-cigarettes have increased quitting rates and therefore reduced smoking prevalence above what would have otherwise been expected (135).…”
Section: Do E-cigarettes Help Smokers Quit or Do They Inhibit Cessation?mentioning
confidence: 99%
“…Although nearly 7 in 10 adult cigarette smokers want to quit [ 3 ], cessation rates remain alarmingly low. For example, the percentage of smokers reporting a serious quit attempt has significantly increased in recent years from 51.2% in 2011 to 55.0% in 2014; however, successful abstinence has remained unchanged at approximately 20% during the same period [ 4 ]. Notably, the number of serious quit attempts is well below the 80% objective outlined in Healthy People 2020 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%